MENU
❌
Home
Math Forum/Help
Problem Solver
Practice
Algebra
Geometry
Tests
College Math
History
Games
MAIN MENU
1 Grade
Adding and subtracting up to 10
Comparing numbers up to 10
Adding and subtracting up to 20
Addition and Subtraction within 20
2 Grade
Adding and Subtracting up to 100
Addition and Subtraction within 20
3 Grade
Addition and Subtraction within 1000
Multiplication up to 5
Multiplication Table
Rounding
Dividing
Perimeter
Addition, Multiplication, Division
4 Grade
Adding and Subtracting
Equivalent Fractions
Divisibility by 2, 3, 4, 5, 9
Area of Squares and Rectangles
Fractions
Equivalent Fractions
Least Common Multiple
Adding and Subtracting
Fraction Multiplication and Division
Operations
Mixed Numbers
Decimals
Expressions
6 Grade
Percents
Signed Numbers
The Coordinate Plane
Equations
Expressions
Polynomials
Polynomial Vocabulary
Symplifying Expressions
Polynomial Expressions
Factoring
7 Grade
Angles
Linear Functions
8 Grade
Linear Functions
Systems of equations
Slope
Parametric Linear Equations
Word Problems
Exponents
Roots
Quadratic Equations
Vieta's Formulas
Progressions
Arithmetic Progressions
Geometric Progression
Progressions
Number Sequences
Reciprocal Equations
Logarithms
Logarithmic Expressions
Logarithmic Equations
Extremal value problems
Trigonometry
Numbers Classification
Geometry
Slope
Intercept Theorem
Law of Sines
Law of Cosines
Vectors
Probability
Limits of Functions
Properties of Triangles
Pythagorean Theorem
Matrices
Complex Numbers
Inverse Trigonometric Functions
Analytic Geometry
Analytic Geometry
Circle
Parabola
Ellipse
Conic sections
Polar coordinates
Home
Practice
Circle, Circle Equations
Circle, Circle Equations: Problems with Solutions
Problem 1
What is the center and radius of the circle $x^{2}+(y-3)^{2}=49$?
Graph the equation.
$C:(0,-3)\qquad r=49$
$C:(3,0)\qquad r=49$
$C:(-3,0)\qquad r=7$
$C:(0,3)\qquad r=7$
Solution:
Answer: center at $(0,3)\qquad r=7$
The canonical form of the circle equation is
$(x-h)^{2}+(y-k)^{2}=r^{2},$ where $C:(h, k)$ and radius $r$
We have $x^{2}+(y-3)^{2}=49,$
$C:(0,3)\qquad r=7$
Problem 2
What is the center and radius of the circle $(x+2)^{2}+y^{2}=36$?
$C:(-2,0)\qquad r=6$
$C:(2,0)\qquad r=\sqrt{6}$
$C:(0,-2)\qquad r=\sqrt{6}$
$C:(0,2)\qquad r=6$
Solution:
The canonical form of the circle equation is
$(x-h)^{2}+(y-k)^{2}=r^{2},$ where the center is at $(h,k)$ and $r$ is its radius.
Our equation is
$(x+2)^{2}+y^{2}=36$
The center is at $(-2,0)$ and the radius is 6.
Problem 3
Complete the square and determine the center and radius of the circle $2x^{2}+2y^{2}+4x+16y+1=0$.
$C(-1,-4)$ and $r=\sqrt{\frac{33}{2}}$
$C(1,4)$ and $r=\sqrt{\frac{33}{2}}$
$C(4,1)$ and $r=17$
$C(4,-1)$ and $r=17$
Solution:
Answer: $C(-1,-4)$ and $r=\sqrt{\frac{33}{2}}$
$2x^{2}+2y^{2}+4x+16y+1=0\Longrightarrow x^{2}+y^{2}+2x+8y+\frac{1}{2}=0$ then
$\left( x+1\right)^{2}+\left( y+4\right)^{2}-1-16+\frac{1}{2}=0\Longrightarrow \left( x+1\right) ^{2}+\left( y+4\right) ^{2}=\frac{33}{2}$
We see that the center is at $(-1,-4)$ and the radius is $\sqrt{\frac{33}{2}}$
Problem 4
Which of the following is the equation of the circle with center at $(2,3)$ and radius $4$? Graph the equation.
$(x-2)^{2}+(y-3)^{2}=4$
$(x+2)^{2}+(y-3)^{2}=16$
$(x-2)^{2}+(y-3)^{2}=16$
$(x-2)^{2}+(y+3)^{2}=4$
Solution:
Answer: $(x-2)^{2}+(y-3)^{2}=16$
The canonical form of the circle equation is $(x-h)^{2}+(y-k)^{2}=r^{2}$, where the center is located at point $(h,k)$ and the radius is $r$
So the equation is $(x-2)^{2}+(y-3)^{2}=4^{2}\Longrightarrow (x-2)^{2}+(y-3)^{2}=16$
Problem 5
Which of the following is the equation of the circle with
center at $(-1, 4)$ and a radius of 4? Graph the equation.
$(x+1)^{2}+(y-4)^{2}=4$
$(x-1)^{2}+(y-4)^{2}=4$
$(x+1)^{2}+(y+4)^{2}=4$
$(x-1)^{2}+(y+4)^{2}=4$
Solution:
The canonical form of the circle equation is
$(x-h)^{2}+(y-k)^{2}=r^{2},$ where the center of the circle is located at point $(h,k)$ and the radius $r$
So $(x+1)^{2}+(y-4)^{2}=2^{2}\Longrightarrow (x+1)^{2}+(y-4)^{2}=4$
Problem 6
The center and radius of the circle $x^{2}+y^{2}-4x+2y=0$ is:
$C(-2,-1)$, $r=\sqrt{5}$
$C(-2,1)$, $r=5$
$C(2,1)$, $r=5$
$C(2,-1)$, $r=\sqrt{5}$
Solution:
We must complete the square, so
$x^{2}+y^{2}-4x+2y=0\Longrightarrow \left( x-2\right)^{2}+\left(y+1\right)^{2}-4-1=0$
then $\left(x-2\right)^{2}+\left( y+1\right)^{2}=5$
We see that
the center is at $(2,-1)$ and the radius $r=\sqrt{5}$.
Problem 7
Which of the following lines is the tangent to the circle $x^{2}+y^{2}-4x-21=0$ at the point $T(5,4)$?
$4y-3x-31=0$
$4x+3y-31=0$
$4y+3x-31=0$
$4y+3x+31=0$
Solution:
Answer: $x^{2}+y^{2}+Dx+Ey+F=0$ where $D=-4\qquad E=0\qquad F=-21$
The equation of the tangent at the point $\left( x_{t},y_{t}\right)=(5,4)$ is
$y-y_{t}=\left( \frac{-2x_{t}-D}{2y_{t}+E}\right) (x-x_{t})$ So
$y-4=\left( \frac{-10+4}{8+0}\right) (x-5)\Longrightarrow y-4=\frac{-3}{4}(x-5)$
$4y+3x-31=0$
Problem 8
What is the equation of a circle with center at $(0,0)$ that passes through $(-1,-2)$?
$x^{2}-y^{2}=\sqrt{5}$
$x^{2}+y^{2}=\sqrt{5}$
$x^{2}-y^{2}=5$
$x^{2}+y^{2}=5$
Solution:
The canonical form of the equation of the circle is
$(x-h)^{2}+(y-k)^{2}=r^{2}$
The center is at point $(0,0)$ and $r$ is its radius.
Then $x^{2}+y^{2}=r^{2}\Longrightarrow r=\sqrt{x^{2}+y^{2}}$
We know that the circle passes through $(-1,-2)$, therefore $r=\sqrt{\left( -1\right)^{2}+\left(-2\right) ^{2}}=\sqrt{5}$
So the equation is $x^{2}+y^{2}=5$
Problem 9
What is the equation of a circle with center at $(4,-5)$ that passes through $(7,-3)$?
$(x-4)^{2}+(y+5)^{2}=13$
$(x+4)^{2}+(y+5)^{2}=13$
$(x-4)^{2}+(y-5)^{2}=13$
$(x-4)^{2}+(y-5)^{2}=13$
Solution:
The canonical form of the equation of the circle is
$(x-h)^{2}+(y-k)^{2}=r^{2},$ where the center is at point $(4,-5)$ and $r$ is its radius.
So $(x-4)^{2}+(y+5)^{2}=r^{2}\Longrightarrow r=\sqrt{(x-4)^{2}+(y+5)^{2}}$ Since the circle passes through $(7,-3)$ then
$r=\sqrt{\left( 3\right)^{2}+\left( 2\right)^{2}}=\sqrt{13}$
So the equation is $(x-4)^{2}+(y+5)^{2}=13$
Problem 10
A circle with center at $(5,6)$ touches x-axis. What is the equation of the circle?
$(x+5)^{2}+(y+6)^{2}=6$
$(x+5)^{2}+(y-6)^{2}=36$
$(x-5)^{2}+(y-6)^{2}=36$
$(x-5)^{2}+(y+6)^{2}=6$
Solution:
Answer: $(x-5)^{2}+(y-6)^{2}=36$
Since the circle touches x-axis, $r=\left\vert y_{c}\right\vert$ where the center is $(x_{c},y_{c})$
So $y_{c}=6$ and the equation is $(x-5)^{2}+(y-6)^{2}=36$
Problem 11
A circle with center at $(-4,3)$ touches y-axis.
What is the equation of the circle?
$(x-4)^{2}+(y-3)^{2}=4$
$(x+4)^{2}+(y+3)^{2}=16$
$(x+4)^{2}+(y-3)^{2}=16$
$(x-4)^{2}+(y+3)^{2}=4$
Solution:
Since the circle is touches y-axis, $r=\left\vert x_{c}\right\vert $ where the center is at $(x_{c},y_{c})$
So $x_{c}=-4$ and the equation is $(x+4)^{2}+(y-3)^{2}=16$
Problem 12
Find the equation of the circle with center $O(-2,3)$ and radius $r=4$. Which of the following points belong to the circle?
$(2,3)$
$(-4,3)$
$(1,5)$
None of these
Solution:
Answer: $(2,3)$
$(x+2)^{2}+(y-3)^{2}=16$
Let we check which of the points satisfies this equation.
$A(2,3):(2+2)^{2}+(3-3)^{2}=16\Longrightarrow 16=16$ then $A(2,3)\in C$
$B(-4,3):(-4+2)^{2}+(3-3)^{2}=16\Longrightarrow 4\neq 16$ then $B(-4,3)\notin C$
$D(1,5):(1+2)^{2}+(5-3)^{2}=16\Longrightarrow 9+4=13\neq 16$ then $D(1,5)\notin C$
Problem 13
What is the equation of the circle with center $O(2,-1)$ that is tangent to the straight line $r:y=x+2$?
Graph the equation.
$(x+2)^{2}+(y+1)^{2}=\frac{25}{2}$
$(x-2)^{2}+(y-1)^{2}=\frac{25}{2}$
$(x-2)^{2}+(y+1)^{2}=\frac{25}{2}$
$(x+2)^{2}+(y-1)^{2}=\frac{25}{2}$
Solution:
Answer: $(x-2)^{2}+(y+1)^{2}=\frac{9}{5}$
We know that the radius $r$ is the distance between $O:(h,k)$ and the straight line $y-x-2=0$
So, $O:(2,-1)$ $r=d(O,L)=\frac{\left\vert -2-1-2\right\vert }{\sqrt{1^{2}+\left( -1\right) ^{2}}}=\frac{5}{\sqrt{2}}$ then the equation of the circle is
$(x-h)^{2}+(y-k)^{2}=r^{2}\Longrightarrow (x-2)^{2}+(y+1)^{2}=\frac{25}{2}$
Problem 14
What is the equation of the circle concentric with circle $(x-2)^{2}+(y+1)^{2}=5$ that is tangent to the line $2x-y+2=0$?
$(x+2)^{2}+(y+1)^{2}=\frac{49}{5}$
$(x-2)^{2}+(y-1)^{2}=\frac{49}{5}$
$(x+2)^{2}+(y+1)^{2}=\frac{7}{5}$
$(x-2)^{2}+(y+1)^{2}=\frac{49}{5}$
Solution:
The concentric circle equation is $(x-2)^{2}+(y+1)^{2}=r^{2}$
We know that the radius $r$ is the distance between the center $O:(h,k)$ to line
So, $O:(2,-1)$ $r=d(C,L)=\frac{\left\vert 2\times 2+1+2\right\vert }{\sqrt{2^{2}+\left( -1\right) ^{2}}}=\frac{7}{\sqrt{5}}=\frac{7}{5}\sqrt{5}$
Then the circle equation is $(x-2)^{2}+(y+1)^{2}=\frac{49}{5}$
Problem 15
Which of the following straight lines is a tangent to the circle $(x-2)^{2}+y^{2}=25$?
$L1:3x+4y-6=0$
$L2:3x+4y-31=0$
$L3:3x+4y-60=0$
$L4: 2x+y+25=0$
Solution:
Answer: L2: $3x+4y-31=0$
A straight line that is a tangent to a circle and the circle itself must have exactly one common point.
So for these lines we obtain $y=\frac{C-3x}{4}$, the substitute $y$ into the equation of the circle so $(x-2)^{2}+\left( \frac{C-3x}{4}\right)^{2}=25$
and now we solve the equation,
$x^{2}-4x+4+\frac{C^{2}-6Cx+9x^{2}}{16}=25\Longrightarrow 16x^{2}-64x+64+C^{2}-6Cx+9x^{2}=400$
then $25x^{2}-(64+6C)x+\left( 64+C^{2}-400\right) =0$
$x=\frac{(64+6C)\pm \sqrt{(64+6C)^{2}-100\left( 64+C^{2}-400\right) }}{50}$
Since $x$ has only one solution (the point of tangency),
then $(64+6C)^{2}-100\left( 64+C^{2}-400\right) =0$ We have three options for $C=6,31,60$
the unique value $C$ which satisfies the previous expression is $C=31$ since $(64+6\cdot 31)^{2}-100\left( 64+31^{2}-400\right) =250^{2}-62500=0$
So L2: $3x+4y-31=0$ is the straight line tangent to the circle.
Submit a problem on this page.
Problem text:
Solution:
Answer:
Your name(if you would like to be published):
E-mail(you will be notified when the problem is published)
Notes
: use [tex][/tex] (as in the forum if you would like to use latex).
Correct:
Wrong:
Unsolved problems:
Contact email:
Follow us on
Twitter
Facebook
Author
Copyright © 2005 - 2020.